Expression of α(2)-adrenergic receptors in rat primary afferent neurones after peripheral nerve injury or inflammation - Birder, L A (Blackwell Science Inc, 1999)
1. Immunocytochemistry with polyclonal antibodies directed against specific fragments of intracellular loops of α(2A)- and α(2C)-adrenergic receptors (α(2A)-AR, α(2C)-AR) was used to explore the possibility that expression of these receptors in dorsal root ganglion (DRG) neurones of rat alters as a result of peripheral nerve injury or localized inflammation. 2. Small numbers of neurones with positive α(2A)-AR immunoreactivity (α(2A)-AR-IR) were detected in DRG from normal animals or contralateral to nerve lesions. In contrast, after complete or partial sciatic nerve transection the numbers of ipsilateral L(4) and L(5) DRG somata expressing α(2A)-AR-IR sharply increased (>5-fold). There was no discernible change in the number of DRG neurones exhibiting α(2A)-AR-IR innervating a region in association with localized chemically induced inflammation. 3. After nerve injury, double labelling with Fluoro-Gold, a marker of retrograde transport from transected fibres, or by immunoreactivity for c-jun protein, an indicator of injury and regeneration, suggested that many of the neurones expressing α(2A)-AR-IR were uninjured by the sciatic lesions. 4. In general the largest proportionate increase in numbers of neurones labelled by α(2A)-AR-IR after nerve lesions appeared in the medium-large diameter range (31–40 μm), a group principally composed of cell bodies of low threshold mechanoreceptors. The number of small diameter DRG neurones labelled by α(2A)-AR-IR, a category likely to include somata of nociceptors, also increased but proportionately less. 5. Relatively few DRG neurones exhibited α(2C)-AR-IR; this population did not appear to change after either nerve lesions or inflammation. 6. These observations are considered in relation to effects of nerve injury on excitation of primary afferent neurones by sympathetic activity or adrenergic agents, sympathetically related neuropathy and reports of sprouting of sympathetic fibres in DRG.